2016
DOI: 10.3897/nl.39.6887
|View full text |Cite
|
Sign up to set email alerts
|

Diasemiopsis ramburialis (Duponchel) (Lepidoptera, Pyralidae s. l., Spilomelinae) in Iran: first record for the country and first host plant report on water fern (Azolla filiculoides Lam., Azollaceae)

Abstract: During a survey at the Rice Research Institute of Iran (RRII, Rasht, Guilan) for potential biocontrol agents of water fern, Azolla filiculoides Lam. (Pteridophyta: Azollaceae), larvae of Diasemiopsis ramburialis (Duponchel) (Pyralidae s. l., Spilomelinae) were discovered feeding on water fern. Larvae were found to cause serious feeding damage on leaves of water fern in the laboratory. The biology, life cycle, and the morphology of all stages of this species are described and illustrated for the first time. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Our finding of Hoploscopinae and Musotiminae in different clades speaks in favour for an independent evolution of fern feeding in these two groups. Further cases of fern feeding in Crambidae are known from Diasemiopsis ramburialis (Duponchel, 1833), Herpetogramma platycapna (Meyrick, 1897) , Samea multiplicalis (Guenée, 1854), Udea decrepitalis (Herrich‐Schäffer, 1848) (all Spilomelinae) and Phenacodes aleuropa (Lower, 1903) (Glaphyriinae), and from several Acentropinae feeding on aquatic pteridophytes (Farahpour‐Haghani et al., 2016; Kirk, 1978; Knopf & Habeck, 1976; Lhomme, 1935; see also Mally et al., 2017 for additional fern‐feeding species).…”
Section: Resultsmentioning
confidence: 99%
“…Our finding of Hoploscopinae and Musotiminae in different clades speaks in favour for an independent evolution of fern feeding in these two groups. Further cases of fern feeding in Crambidae are known from Diasemiopsis ramburialis (Duponchel, 1833), Herpetogramma platycapna (Meyrick, 1897) , Samea multiplicalis (Guenée, 1854), Udea decrepitalis (Herrich‐Schäffer, 1848) (all Spilomelinae) and Phenacodes aleuropa (Lower, 1903) (Glaphyriinae), and from several Acentropinae feeding on aquatic pteridophytes (Farahpour‐Haghani et al., 2016; Kirk, 1978; Knopf & Habeck, 1976; Lhomme, 1935; see also Mally et al., 2017 for additional fern‐feeding species).…”
Section: Resultsmentioning
confidence: 99%
“…Since then, the overall ecological water quality, the habitat conditions, the numbers of migratory birds and fishes, and the aquatic plant diversity have declined in this ecosystem, particularly in the protected Selkeh wildlife refuge (Sadeghi et al 2013a, b). In addition, the Amir-Kelayeh Wetland, which is another wildlife refuge, has become infested by this annoying weed as well (Farahpour et al 2016). These changes are mainly related to anthropogenic activities (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, it has been indicated that Diasemiopsis ramburialis (Duponchel, 1833) and Nomophila noctuella (Denis and Schiffermuller, 1775) (Figure 1), two snout moths from spilomelinae, feed on Azolla spp. in the northern region of Iran and have overlapping feeding periods (Table 1) [2,3]. Diasemiopsis was described by Munroe (1957) with Hydrocampa ramburialis (Duponchel, 1833) as type species.…”
Section: Introductionmentioning
confidence: 99%
“…Diasemiopsis ramburialis is a cosmopolitan species [5] and Azolla spp. are known as the first host plants of this moth [2]. Nomophila was described by Hübner (1825) with Pyralis hybridalis (Hübner, 1796) as type species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation